Long term outcome after a first myocardial infarction. (14th October 2021) - Almosawi, M; Ferrannini, G; Buhlin, K; Gustafsson, A; Kjellstrom, B; Klinge, B; Nygren, Å; Nasman, P; Svenungsson, E; Ryden, L; Norhammar, A
Abstract: Background: Prognosis after a myocardial infarction (MI) have improved consistently over the last decades. In parallel, the incidence of cardiovascular (CV) events has been reduced and life expectancy in people free from CV disease improved. Purpose: To explore the long-term mortality and burden of cardiovascular disease in patients after a first MI compared to matched controls in a contemporary setting. Methods: The Swedish case-control study PAROKRANK recruited 805 patients <75 years with a first MI and 805 age-, gender- and area-matched controls from 2010 to 2014. All participants were followed by means of registry-based information. The primary endpoint was the first of a composite of all-cause death, non-fatal MI, non-fatal stroke and heart failure hospitalization. Data on the outcomes were provided via linkage to the National Patient Registries and the Cause of Death Registry. Hazard Ratios (HR) for the first composite event were calculated by means of a Cox regression model, subsequently adjusted for smoking, education level and marital status at baseline. Event curves for the time-to-first event in patients and controls were computed by Kaplan-Meier curves and the two groups were compared by means of the log-rank test. Results: Data from 804 patients and 800 controls (mean age in both groups 62 years; women 19%) were complete for an average period of 6.2 years (0.2–8.5 years). The total number of events was 211. Patients had a higher event rate than controls (log rank p<0.0001). Unadjusted HR for the primary outcome was 2.08 (95% confidence interval (CI) 1.56–2.77) while the adjusted HR was 2.04 (95% CI 1.52–2.73). Mortality did not differ significantly between patients (n=38; 4.7%) and controls (n=35; 4.4%). In total, 82.5% of the patients and 91.3% of the controls were event-free during follow-up. Conclusion: This long-term follow-up of a contemporary, nationwide case-control cohort illustrates that the likelihood for CV events is higher in patients with a first MI compared to their matched controls while mortality did not differ. The access to high quality of care and cardiac rehabilitation might explain the low rates of adverse outcomes. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): AFA Insurance, Swedish Heart-Lung Foundation, Swedish Research Council, Swedish Society of Medicine, Stockholm County Council (ALF project and Steering committee KI/SLL for odontological research), and The Baltic Child Foundation.